2018
DOI: 10.3897/zookeys.811.28712
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of the European Butterflies (Lepidoptera, Papilionoidea)

Abstract: This paper presents an updated checklist of the butterflies of Europe, together with their original name combinations, and their occurrence status in each European country. According to this checklist, 496 species of the superfamily Papilionoidea occur in Europe. Changes in comparison with the last version (2.6.2) of Fauna Europaea are discussed. Compared to that version, 16 species are new additions, either due to cryptic species most of which have been discovered by molecular methods (13 cases) or due to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 41 publications
2
130
0
Order By: Relevance
“…We analysed 403 butterfly species recorded from the 28 member states of the European Union (excluding all non‐European species, as the Macaronesian island endemics, for biogeographical reasons, as well as recently acknowledged cryptic species and taxa recently discovered by molecular techniques, see Wiemers et al ., ). We excluded species extinct in Europe prior to World War II, temporary vagrants, and those that are not constantly established.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We analysed 403 butterfly species recorded from the 28 member states of the European Union (excluding all non‐European species, as the Macaronesian island endemics, for biogeographical reasons, as well as recently acknowledged cryptic species and taxa recently discovered by molecular techniques, see Wiemers et al ., ). We excluded species extinct in Europe prior to World War II, temporary vagrants, and those that are not constantly established.…”
Section: Methodsmentioning
confidence: 97%
“…the Red List criteria, Rodrigues et al ., ; prioritizing orchids across Europe, Gauthier, Debussche & Thompson, ). Butterflies (such as a few other invertebrate groups, but mostly vertebrate groups and vascular plants) allow a rigorous test due to the fact that their taxonomy, distribution and ecology are well understood (Settele et al ., ; Tshikolovets, ; Kudrna, Pennerstorfer & Lux, ; Wiemers et al ., ). Furthermore, studies showed that butterflies are increasingly suffering from global change across Europe, and current conservation strategies may fail to counteract this negative trend (see Delpon et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…No specimen collection was carried out due to conservation considerations and was not necessary since the species could not be confused with other lycaenids and detailed photos were taken. Taxonomy and nomenclature follow Wiemers et al (2018) for the butterfly fauna, Hassler et al (2019) and Kleinsteuber et al (2016) for the flora. All photographs and videos by Christos Galanos.…”
Section: Methodsmentioning
confidence: 99%
“…List of butter y species (nomenclature and system:Wiemers et al, 2018) recorded from the former Milovice military training range during the three consecutive surveys, split into respective localities if possible, with their Czech Republic red-list [RL] status (NT -near threatened, VUvulnerable, EN -endangered, CR -critically endangered) following…”
mentioning
confidence: 99%